RUANG IJTIHAD DALAM AMALAN FATWA DI MALAYSIA: SOROTAN DARI SUDUT PENTADBIRAN FATWA - Abd Rahman, Noor Naemah (Jurnal Syariah, 2019)
This article is a survey of the utilization of ijtihad in the issuing of fatwa in Malaysia. The finding had shown that several positive achievements pertaining to the practice of ijtihad has been peiformed by the fatwa institution in Malaysia. Such achievement can be observed in several items, as far as the organization perspectives were concerned. It including (i) the provision imposed to a Mufti to conduct an academic legal research before issuing any fatwa (ii) the provision that extended the prerogative power of the Mufti (iii) the provision that extended the application of moderate and liberal approach in choosing the right mazhab in issuing anyfatwa.